Comparative Evaluation of Hardness in Ceramic Reinforced, Resin Modified Glass Ionomer Cement and Conventional Glass Ionomer Cement - Sushmita Shivanna; Samuel Roshan; S Sameera; Murali Sivakumar; Megavarnan Ravi; Sarvesh LS Ram (Journal of Pharmacy and Bioallied Sciences, 2025)
Aim and Background: This study compares the hardness of ceramic-reinforced glass ionomer cement (Amalgomer CR), resin-modified glass ionomer cement (RMGIC), and conventional glass ionomer cement (GIC) using Vicker’s microhardness tester. Materials and Methods: Nine disc-shaped specimens (5mm diameter, 2mm thickness) were prepared from three materials: Group A (GIC), Group B (Amalgomer CR), and Group C (RMGIC). Hardness was tested after 24 hours of storage at room temperature. Result: Group B showed the highest mean hardness (66.13±5.25), followed by Group A (65.63±8.07) and Group C (62.13±13.70). Differences were not statistically significant. Conclusion: Although Amalgomer CR exhibited slightly higher hardness due to its ceramic component, the differences among the materials were not statistically significant. Clinical significance: Hardness is a key property for dental restorations, ensuring durability by resisting deformation and maintaining integrity during mastication.